Manajemen Pelatihan ASN KESDM dan Industri di Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi Cepu - Sari, Kamilanissa Trisna Ayu Yunita; Lintang Anggraeni; Eli Masidah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the training management for State Civil Apparatus (ASN) of the Ministry of Energy and Mineral Resources (ESDM) and industrial workers at the Center for Human Resources Development of Oil and Gas (PPSDM Migas) Cepu. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews, and literature studies. The results show that human resource management at PPSDM Migas is implemented systematically through the stages of planning, organizing, implementing, and evaluating training. There are different approaches between training for ASN and training for industry. ASN training is more structured following government regulations, while industrial training is more flexible and tailored to specific company needs through cooperation mechanisms such as Cooperation Agreements and tailor-made training. The application of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) serves as the main framework in training development. Factors influencing training effectiveness include material quality, instructor competence, learning methods, facility support, and post-training evaluation. Challenges faced include the complexity of the energy sector, technological developments, environmental impacts, and budget constraints.